2023
DOI: 10.1186/s40644-022-00518-7
|View full text |Cite
|
Sign up to set email alerts
|

Variability of radiotherapy volume delineation: PSMA PET/MRI and MRI based clinical target volume and lymph node target volume for high-risk prostate cancer

Abstract: Purpose A comparative retrospective study to assess the impact of PSMA Ligand PET/MRI ([68 Ga]-Ga-PSMA-11 and [18F]-F-PSMA-1007 PET/MRI) as a new method of target delineation compared to conventional imaging on whole-pelvis radiotherapy for high-risk prostate cancer (PCa). Patients and methods Forty-nine patients with primary high-risk PCa completed the whole-pelvis radiotherapy plan based on PSMA PET/MRI and MRI. The primary endpoint compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Mahase et al observed that the use of [ 68 Ga]-DOTATATE PET/MRI, which can result in a reduction of GTV, consequently leading to a decrease in both clinical tumor volume (CTV)—comprising the GTV and potentially invaded tissues and planning target volume (PTV), which is derived from the expansion of CTV [ 59 ]. In addition, in the lymph node metastasis delineation, the nodal GTV (GTVnd) delineated based on PSMA PET/MRI contains metastatic pelvic lymph nodes more accurately than MRI [ 62 ]. However, Liu et al showed that the CTVs of PSMA PET/MRI and MRI are similar in the target delineation of pelvic lymph node metastasis [ 62 ], where the distinction brought about by GTVnd is not apparent, possibly because CTV encompasses a larger range than GTVnd.…”
Section: Radiotherapy Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Mahase et al observed that the use of [ 68 Ga]-DOTATATE PET/MRI, which can result in a reduction of GTV, consequently leading to a decrease in both clinical tumor volume (CTV)—comprising the GTV and potentially invaded tissues and planning target volume (PTV), which is derived from the expansion of CTV [ 59 ]. In addition, in the lymph node metastasis delineation, the nodal GTV (GTVnd) delineated based on PSMA PET/MRI contains metastatic pelvic lymph nodes more accurately than MRI [ 62 ]. However, Liu et al showed that the CTVs of PSMA PET/MRI and MRI are similar in the target delineation of pelvic lymph node metastasis [ 62 ], where the distinction brought about by GTVnd is not apparent, possibly because CTV encompasses a larger range than GTVnd.…”
Section: Radiotherapy Planningmentioning
confidence: 99%
“…In addition, in the lymph node metastasis delineation, the nodal GTV (GTVnd) delineated based on PSMA PET/MRI contains metastatic pelvic lymph nodes more accurately than MRI [ 62 ]. However, Liu et al showed that the CTVs of PSMA PET/MRI and MRI are similar in the target delineation of pelvic lymph node metastasis [ 62 ], where the distinction brought about by GTVnd is not apparent, possibly because CTV encompasses a larger range than GTVnd. Moreover, the pathological analysis also confirmed the advantage of PET/MRI in the target delineation, Zhang et al proposed that PET/MRI is more adept at mapping GTV by comparing the Dice Similarity Coefficient (DSC) of PET/MRI and PET.…”
Section: Radiotherapy Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FDG-avid lesions potentially could be dose-escalated simultaneously, allowing greater dose delivery while minimizing dose to the surrounding critical structures such as the duodenum. PET/MRI imaging is also being evaluated in other such as prostate and head and neck for target delineation, initial staging, and treatment response assessment (3)(4)(5). We await to see whether PET/MRI could be incorporated into routine radiation oncology practice.…”
Section: Introductionmentioning
confidence: 99%